Pre-treatment with caffeic acid-phthalimide prevents UVB-induced oxidative stress and cytotoxicity - da Silva, Bruna Terra Alves; Chagas, Virgínia Santos; Rodrigues, Renata Bufollo; Ximenes, Valdecir Farias [UNESP]; Nakamura, Celso Vataru; Sueli de Oliveira Silva, Lautenschlager (Springer Nature, 2025)
Prolonged exposure to Ultraviolet B (UVB) rays increases oxidative stress, causes direct DNA photolesions—particularly cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6-4) pyrimidone photoproducts (6-4PPs)—and activates aging-related signaling pathways, leading to skin photoaging and an increased risk of skin cancer. UVB triggers a cascade of enzymatic reactions, notably through nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase), perpetuating the production of reactive oxygen species (ROS) even after exposure has ceased. While numerous studies have explored antioxidant compounds in ameliorating UVB-induced damage, caffeic acid-phthalimide (CF) stands out not only for its antioxidant potential but also for its hydrophobic nature, UVB absorption capacity, particularly within the range of 300–350 nm, and its ability to inhibit NADPH oxidase 2 (NOX2), a key enzyme in oxidative stress. This dual action—physicochemical absorption of UVB and intracellular antioxidant activity—supports CF’s photoprotective potential. Therefore, we investigated the effects and potential mechanisms of CF action on L-929 fibroblasts in response to UVB-induced oxidatively generated damage. Our investigations demonstrated CF’s notable antioxidant activity, as evidenced by results from both the 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and xanthine oxidase (XO) assays. Notably, CF improved the viability of UVB-irradiated L-929 cells and exhibited no cytotoxicity in non-irradiated fibroblasts. CF effectively reduced ROS generation and restored the antioxidant defense system in UVB-irradiated L-929 fibroblasts. Furthermore, CF pre-treatment prevented lipid peroxidation, mitochondrial membrane depolarization, and reduced DNA condensation and apoptosis induced by UVB exposure. CF prevented cell membrane disruption and enhanced the migratory capacity of L-929 fibroblasts. Our study indicates that integrating CF into topical delivery systems holds significant promise as a strategy to counteract UVB-induced oxidatively generated damage in L-929 fibroblasts.